HomeLab: Shared Infrastructure for Home Technology Field Studies - Brush, A.J.; Jung, Jaeyeon; Mahajan, Ratul; Scott, James (UbiComp'12 Workshop on Systems and Infrastructure for the Digital Home (HomeSys), 2012)
Researchers who develop new home technologies using connected devices (e.g. sensors) often want to conduct large-scale field studies in homes to evaluate their technology, but conducting such studies today is quite challenging, if not impossible. Considerable custom engineering is required to ensure hardware and software prototypes work robustly, and recruiting and managing more than a handful of households can be difficult and cost-prohibitive. To lower the barrier to developing and evaluating new technologies for the home environment, we call for the development of a shared infrastructure, called HomeLab. HomeLab consists of a large number of geographically distributed households, each running a common, flexible framework (e.g., HomeOS [4]) in which experiments are implemented. The use of a common framework enables engineering effort, along with experience and expertise, to be shared among many research groups. Recruitment of households to HomeLab can be organic: as a research group recruits (a few) households to participate in its field study, these households can be invited to join HomeLab and participate in future studies conducted by other groups. As the pool of households participating in HomeLab grows, we hope that researchers will find it easier to recruit a large number of households to participate in field studies.